A dual-species co-cultivation system to study the interactions between Roseobacters and dinoflagellates - Wang, Hui; Tomasch, Jürgen; Jarek, Michael; Wagner-Döbler, Irene (Frontiers in Microbiology, 2014)
Some microalgae in nature live in symbiosis with microorganisms that can enhance or inhibit growth, thus influencing the dynamics of phytoplankton blooms. In spite of the great ecological importance of these interactions, very few defined laboratory systems are available to study them in detail. Here we present a co-cultivation system consisting of the toxic phototrophic dinoflagellate Prorocentrum minimum and the photoheterotrophic alphaproteobacterium Dinoroseobacter shibae. In a mineral medium lacking a carbon source, vitamins for the bacterium and the essential vitamin B12 for the dinoflagellate, growth dynamics reproducibly went from a mutualistic phase, where both algae and bacteria grow, to a pathogenic phase, where the algae are killed by the bacteria. The data show a “Jekyll and Hyde” lifestyle that had been proposed but not previously demonstrated. We used RNAseq and microarray analysis to determine which genes of D. shibae are transcribed and differentially expressed in a light dependent way at an early time-point of the co-culture when the bacterium grows very slowly. Enrichment of bacterial mRNA for transcriptome analysis was optimized, but none of the available methods proved capable of removing dinoflagellate ribosomal RNA completely. RNAseq showed that a phasin encoding gene (phaP1) which is part of the polyhydroxyalkanoate (PHA) metabolism operon represented approximately 10 % of all transcripts. Five genes for aerobic anoxygenic photosynthesis were down-regulated in the light, indicating that the photosynthesis apparatus was functional. A betaine-choline-carnitine-transporter (BCCT) that may be used for dimethylsulfoniopropionate (DMSP) uptake was the highest up-regulated gene in the light. The data suggest that at this early mutualistic phase of the symbiosis, PHA degradation might be the main carbon and energy source of D. shibae, supplemented in the light by degradation of DMSP and aerobic anoxygenic photosynthesis.